γ-Aminobutyric acid treatment enhances quality and improves antioxidant activities of fresh-cut Euryale ferox stems during postharvest storage - Wang, Yan; Wei, Hongmei; Wang, Songxu; Yu, Fulong; Zhai, Ligong; Yang, Jianting; Wei, Zhaohui (Frontiers in Nutrition, 2025)
IntroductionFresh-cut Euryale ferox stem (FCEFS) is a nutrient-rich but underutilized vegetable that has a short shelf life, making it prone to softening and rotting.MethodsThe effects of different concentrations of γ-aminobutyric acid (GABA) on sensory quality and antioxidant activity during cold storage at 4°C for 20 d were examined.ResultsThe results revealed that the FCEFS samples treated with 5 mM GABA maintained greater hardness and ascorbic acid, total phenolic compound and chlorophyll contents than the FCEFS samples not treated with GABA. FCEFS samples subjected to GABA treatment and stored under long-term cold storage conditions presented elevated sensory scores. The control group had ceased to possess commercial value on 16 d, and it was edible by 20 d following GABA treatment, which was corroborated by the notable colour characteristics and electronic nose analysis. Notably, GABA treatment delayed the decrease in soluble solid and endogenous GABA levels, and delayed the accumulation of malondialdehyde and the increase in lignin content in FCEFS during cold storage. In addition, GABA maintained high peroxidase (POD), superoxide dismutase (SOD), ascorbate peroxidase (APX) and phenylalanine ammonia lyase (PAL) activities.DiscussionTreatment with 5 mM GABA maintained the shelf-life and sensory quality of the FCEFS for 20 d at 4°C. Therefore, these results indicate that GABA can be used to delay the softening of FCEFS and extend its cold storage and shelf-life.